Status of soil nutrients and its relation with rock types and soil properties in the Kankali (Chitwan) and Tibrekot (Kaski) Community Forests, western Nepal (Journal of Nepal Geological Society, 2013)
This study was conducted in Kankali (Chitwan) and Tibrekot (Kaski) Community Forests to explore the status of soil nutrients and its relation with rock types and physical and chemical properties of soils. The soil sample data collected from the community forests were analyzed for soil texture, soil pH, soil organic matter (SOM), N, P, K, Zn and boron using reliable equipment and standard methods. The data are interpreted by applying descriptive statistics. The inter-relationship between soil nutrients is presented at 99% and 95% confidence levels. N, P, Zn and B show direct and indirect relation with soil texture. K, Zn and B show both positive and negative correlation with soil pH. SOM also show direct and indirect relation with NPK and Zn. The relations of soil texture, SOM, soil pH, N, P, K, Zn and B with rocks are interpreted using nutrient element content in minerals of studied rocks. This paper presents clear and consistent evidences of the role of soil nutrients in shaping the vegetation growth pattern and their distribution in the middle Mountain and Siwalik physiographic regions of Nepal.